qanda-logo
search-icon
root-icon-orangeSímbolos
Problema
solution-image
$1.\right)$ $\left(2x^{3}\right)-\left(5x^{3}\right)=$ $2.\right)$ $\left(12x^{3}\right).\left(4x\right)=$ $3.\right)$ $5.\left(2x^{2}y^{3}z\right)=$ $4.\right)$ $\left(5x^{2}y^{3}z\right).\left(2y^{2}z^{2}\right)=$ $5.\right)$ $\left(18x^{3}y^{2}z^{5}\right).\left(6x^{3}yz^{2}\right)=$ $6.\right)$ $\left(-2x^{3}\right).\left(-5x\right).\left(-3x^{2}\right)=$
Bachillerato
Aritmética y álgebra
Búsquedas: 138
Contenido de la pregunta
me ayudaría por favor
Solución
answer-user-profile-image
Profesor de Qanda - Jersey
answer-reply-image
answer-reply-image
answer-user-profile-image
Estudiante
gracias
Problemas similares